2016
DOI: 10.29122/jbbi.v3i2.72
|View full text |Cite
|
Sign up to set email alerts
|

PENGARUH AUKSIN DAN SITOKININ TERHADAP PERBANYAKAN MIKRO TANAMAN BINAHONG (<i>Anredera cordifolia</i> (Tenore) Steenis)

Abstract: EFFECT OF AUXIN AND CYTOKININ ON MICROPROPAGATION OF BINAHONG (Anredera cordifolia (Tenore) Steenis)Binahong (Anredera cordifolia (Tenore) Steenis) is known as miraculous medicinal plant for its potential to cure for various kinds of diseases such as diabetes, stabilizing blood pressure and circulation, accelerating wound healing, and preventing stroke. In order to provide high quality seedlings of this medicinal plant continuously in large amount, the study on binahong micropropagation was performed. Plant gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 0 publications
0
3
0
5
Order By: Relevance
“…This was probably be due to too high levels of auxin and cytokinin contained in the mung bean sprouts. According to the finding of Suparjo et al (2016), high concentration of auxin or cytokinin reduced the growth of binahong plants and may also occur in pineapple plants. Extract mung bean sprouts of 12.5% increased the growth of aloe vera plants (Rita et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…This was probably be due to too high levels of auxin and cytokinin contained in the mung bean sprouts. According to the finding of Suparjo et al (2016), high concentration of auxin or cytokinin reduced the growth of binahong plants and may also occur in pineapple plants. Extract mung bean sprouts of 12.5% increased the growth of aloe vera plants (Rita et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Hasil penelitian Sugiyarto & Kuswandi (2014) mengenai pertumbuhan kalus pada daun binahong hijau menunjukkan bahwa pemberian 1 ppm 2,4-D mampu menghasilkan pembentukan kalus tercepat. Menurut Suparjo et al (2016) pemberian kinetin pada pertumbuhan kalus daun binahong hijau menghasilkan kalus terbesar pada konsentrasi 0,5 ppm. Khaniyah et al (2012) menyatakan bahwa penambahan 0,5 ppm 2,4-D dengan 1 ppm kinetin menghasilkan persentase berkalus tertinggi pada daun dewa (Gynura procumbens L.).…”
Section: Pendahuluanunclassified
“…Shallot extract contains auxin in the form of IAA (Indoleacetic acid). Research by Suparjo et al (2016) showed the influence of IAA on shoot height and number of leaves of binahong plants through micro propagation.…”
Section: Number Of Rootsmentioning
confidence: 99%